Liver metastases: Analysis of survival and the value of systematic chemotherapy in adenocarcinomas - Viola Alles, Alberto; Ortega, Betys; Leivobici, Simón (Cirugía del Uruguay, 1982)
The authors study the incidence of hepatic metastasis in a series of 1049 patients bearing tumors of different histopathology; centering the analysis on digestive and genital adenocarcinomas . In this group th e incidence reached 29 'lo. The longest mean survival time was found in ovary tumors: 12.7 months; and the shortest mean survival time was found in pancreatic tumors: 2 months. The authors analyze the therapeutical effect of the systemic chemotherapy admirristered, which seems to lengthen the survival time, however without a statistical significance. Finally the authors speak about the need for a clinical stratification of these patients in order to give a better treatment orientation and to mark the general therapy guidelines.